Exploring Teachers’ Perceptions of EFL Students’ Engagement in Collaborative Learning: Implementation Issues and Suggestions - Ali Abbas Falah Alzubi; Mohd Nazim; Jalal Ahmad (Qubahan Academic Journal)
The evolving landscape of collaborative learning in English education for the last two decades has witnessed a notable research surge in diverse contexts. Nevertheless, empirical evidence suggests a noticeable dearth of attention or very limited emphasis, particularly within the setting of Arabic-native speaking countries on exploring English teachers’ perceptions concerning students' engagement in collaborative learning. Therefore, this study aims to identify teachers’ perceptions of EFL students’ engagement in collaborative learning with a special reference to implementation issues and solutions to address the challenges. The descriptive survey design was employed to attain the study objectives. A sample of (45) EFL teachers chosen following the convenient sampling method answered a closed-item questionnaire and did an interview. The results revealed that EFL teachers highly perceived implementing collaborative learning among university students in EFL classrooms. Also, the respondents’ teaching experiences did not impact their perceptions of implementing collaborative learning in EFL classrooms. In addition, gender did not play any role in affecting the respondents’ answers to implementing collaborative learning in EFL classrooms. Finally, the analysis of interview contents showed that the problems that teachers face in implementing collaborative learning include diverse language proficiency, cultural differences, impartial participation, personal conflicts, limited class time, access to resources, and lack of professional development. Additionally, the participants suggested differentiated teaching, encouraged participation, efficient time management, language skill grouping, and EFL-specific teacher training to make a collaborative learning environment effective.